THE COMPUTING PROGRAM OF A DYNAMICS IN PASSENGER CAR - Pshinko, O. M.; Myamlin, S. V. (Science and Transport Progress, 2005)
In article the description of algorithm of drawing up of the program of calculations of dynamic indexes of the carriage with use of object-oriented simulation which was used for performance of theoretical researches of carriages with various characteristics is resulted.